2021
DOI: 10.1111/cbdd.13864
|View full text |Cite
|
Sign up to set email alerts
|

Development and characterization of two novel 68Ga‐labelled neuropeptide Y short analogues with potential application in breast cancer imaging

Abstract: In vivo receptor targeting with radiolabelled peptide‐based probes is an attractive approach for the development of novel radiotracers for molecular imaging. This work presents the development and characterization of two novel neuropeptide Y analogues labelled with a positron emitter 68Ga, for potential use in breast cancer imaging. Both analogues share the same amino acid sequence and were derivatized with NOTA through either a lysine linker (L1) or an acetylated lysine (L2). In both cases, a single product w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…The development of multifunctional NPY-conjugates for selective nuclear delivery of radio lanthanides (targeted radionuclide therapy) is a promising strategy to deliver therapeutically active cargos (e.g., radiometals) into tumor cells overexpressing peptide receptors (e.g., Y1R) [ 255 ]. Novel 68 Ga-labeled NPY, short analogs with potential applications in cancer imaging, have been developed [ 256 ]. Moreover, 99 mTc-labeled NPY short analogs showing Y1R affinity and potential applications in cancer imaging have been reported: in vitro studies demonstrated a specific cellular uptake and a high internalization rate, whereas the IC 50 was 73.2 nM [ 257 ].…”
Section: Antitumor Therapeutic Strategiesmentioning
confidence: 99%
“…The development of multifunctional NPY-conjugates for selective nuclear delivery of radio lanthanides (targeted radionuclide therapy) is a promising strategy to deliver therapeutically active cargos (e.g., radiometals) into tumor cells overexpressing peptide receptors (e.g., Y1R) [ 255 ]. Novel 68 Ga-labeled NPY, short analogs with potential applications in cancer imaging, have been developed [ 256 ]. Moreover, 99 mTc-labeled NPY short analogs showing Y1R affinity and potential applications in cancer imaging have been reported: in vitro studies demonstrated a specific cellular uptake and a high internalization rate, whereas the IC 50 was 73.2 nM [ 257 ].…”
Section: Antitumor Therapeutic Strategiesmentioning
confidence: 99%
“…More recently, still focusing on in vivo receptor targeting with radiolabeled peptidebased probes, Cardoso et al described the development and characterization of two 68 Ga-labeled NPY analogues for their potential use in breast cancer diagnosis [134]. Both of the analogues shared the same amino acid sequence: Tyr-Arg-Leu-Arg-BPA-Nle-Pro-Asn-Ile (BPA: L-4-benzoylphenylalanine), one which favors preferential binding to NPY Y 1 receptors, and were derivatized with NOTA (Figure 10) through a lysine (35a) or an acetylated lysine (35b) linker.…”
Section: Npy Y1 Receptormentioning
confidence: 99%
“…Both of the analogues shared the same amino acid sequence: Tyr-Arg-Leu-Arg-BPA-Nle-Pro-Asn-Ile (BPA: L-4-benzoylphenylalanine), one which favors preferential binding to NPY Y 1 receptors, and were derivatized with NOTA (Figure 10) through a lysine (35a) or an acetylated lysine (35b) linker. More recently, still focusing on in vivo receptor targeting with radiolabeled peptidebased probes, Cardoso et al described the development and characterization of two 68 Galabeled NPY analogues for their potential use in breast cancer diagnosis [134]. Both of the analogues shared the same amino acid sequence: Tyr-Arg-Leu-Arg-BPA-Nle-Pro-Asn-Ile (BPA: L-4-benzoylphenylalanine), one which favors preferential binding to NPY Y1 receptors, and were derivatized with NOTA (Figure 10) through a lysine (35a) or an acetylated lysine (35b) linker.…”
Section: Npy Y1 Receptormentioning
confidence: 99%